Penerapan Digital Marketing Sebagai Optimalisasi Dalam Meningkatkan Hasil Penjualan Usaha Mikro Kecil dan Menengah (UMKM) Air Haji Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan - Dike Rama Putra; Rahmatullah Pratama; Widia Firta (CV. ITTC INDONESIA, 2025)
The Air Haji is a village that produces many types of MSME products based on initial observations found that partners still carry out marketing activities with a manual system in selling their products, this is because it is not that partners reject digital marketing but they do not understand how to use digital marketing. Therefore, Community Service activities aim to invite and socialize the use of digital marketing in increasing MSME Sales. The method of implementing PKM by providing training, mentoring by using their respective Android HP Media, then installing several applications that support the sales process of their MSME Products later, so that partners better understand the use of digital marketing conducted discussion and question and answer sessions. The results achieved show success seen from the way partners use and utilize digital marketing, through their respective anroid cellphones the conclusion of this activity provides knowledge to partners can innovate and be creative in entrepreneurship through digital marketing in increasing sales of MSME products independently